Meaningful work and resilience among teachers: The mediating role of work engagement and job crafting - Van Wingerden, Jessica (PLoS One, 2019)
Research in the field of work and organizational psychology more and more highlights the importance of employees’ experience of meaningful work. Adding to this area of research, the present study among teachers examined the relationship between meaningful work and resilience and tested whether this proposed relationship is mediated by teachers’ work engagement and job crafting behaviour. Data for this study was collected among a group of Dutch teachers working in a school for primary education (N = 174). To test the hypothesized relationships, we conducted a bootstrapping analysis. The outcomes revealed that work engagement and job crafting fully mediated the relationship between meaningful work and teacher’s resilience. The insights provided in this study may be useful for the deliberate cultivation of teachers’ resilience and may help them to stay enthusiastic in their meaningful but demanding profession. Theoretical contributions, limitations, suggestions for future research and practical implications are discussed.